From Kyai to Politicians: The Intellectual-Political Journey of K.H. Abdurrahman Chudlori 1943-2011 - Khoirul Murti Ulfiyah (Journal of Nahdlatul Ulama Studies, 2021)
K.H Abdurrahman Chudlori is the caretaker of the Tegalrejo Islamic Boarding School Boarding School, Magelang. K.H Abdurrahman Chudlori became one of the influential figures in Magelang, especially in Tegalrejo. K.H Abdurrahman Chudlori also played an active role in society. In addition, K.H Abdurrahman Chudlori is also active in political parties, even being one of the founders of the PKNU Party. In this research, the author uses historical research methods that include collecting sources in written and oral, source criticism, interpretation or interpretation, and writing history or historiography. The results of this study are; (1) K.H. Abdurrahman Chudlori is a persistent learning person, a figure who becomes a role model for the community because he cares for the community very high, always prioritizes the welfare of the community (2) K.H. Abdurrahman Chudlori is the caretaker of the large Islamic Boarding School Magelang Islamic Education Dormitory, Kyai who has a charismatic figure, (3) K.H. Abdurrahman Chudlori is active in the NU Ormas, he is also active in three political parties and is one of the founders of the PKNU Party.